\sqrt{2};}} \right. \\ (2^2)^{\sqrt{x^2-2}+x}-5\cdot2^{-1}\cdot2^{\sqrt{x^2-2}+x}=6, \\ (2^{\sqrt{x^2-2}+x})^2-\frac{5}{2}\cdot2^{\sqrt{x^2-2}+x}=6, \\ 2^{\sqrt{x^2-2}+x}=u, \ u\ \textgreater \ 0, \\ u^2-2,5u=6, \\ 2u^2-5u-12=0, \\ D=121, \\ u_1=-1,5, \ u_2=4, \\ u=4, \\ 2^{\sqrt{x^2-2}+x}=4, \\ 2^{\sqrt{x^2-2}+x}=2^2, \\ \sqrt{x^2-2}+x=2, \\ \sqrt{x^2-2}=2-x, \\ 2-x\geq0, \ x\leq2, \\ x^2-2=(2-x)^2, \\ x^2-2=4-4x+x^2, \\ 4x=6, \\ x=1,5." alt="4^{\sqrt{x^2-2}+x}-5\cdot2^{\sqrt{x^2-2}+x-1}=6, \\ x^2-2\geq0, \ (x-\sqrt{2})(x+\sqrt{2})\geq0, \ \left [ {{x<-\sqrt{2},} \atop {x>\sqrt{2};}} \right. \\ (2^2)^{\sqrt{x^2-2}+x}-5\cdot2^{-1}\cdot2^{\sqrt{x^2-2}+x}=6, \\ (2^{\sqrt{x^2-2}+x})^2-\frac{5}{2}\cdot2^{\sqrt{x^2-2}+x}=6, \\ 2^{\sqrt{x^2-2}+x}=u, \ u\ \textgreater \ 0, \\ u^2-2,5u=6, \\ 2u^2-5u-12=0, \\ D=121, \\ u_1=-1,5, \ u_2=4, \\ u=4, \\ 2^{\sqrt{x^2-2}+x}=4, \\ 2^{\sqrt{x^2-2}+x}=2^2, \\ \sqrt{x^2-2}+x=2, \\ \sqrt{x^2-2}=2-x, \\ 2-x\geq0, \ x\leq2, \\ x^2-2=(2-x)^2, \\ x^2-2=4-4x+x^2, \\ 4x=6, \\ x=1,5." align="absmiddle" class="latex-formula">